THE EFFECT OF ANKLE AND SUBTALAR JOINT SOMATIC DYSFUNCTION CORRECTION TO IMPROVE ORIENTEER STATIC BALANCE - Smila, Baiba; Fernāte, Andra; Zaļaiskalna, Velga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The most frequent injuries among sports orienteers are the ankle injuries. The one of the most effective means to prevent the ankle injuries and recurrent ankle injuries is balance and stability development. The aim of this study is to find out the most effective method to develop static stability in the previously injured ankle for orienteers: osteopathic treatment of the ankle and subtalar joints or balance exercises, or the combination of osteopathic treatment of the ankle and subtalar joints and balance exercises. The effectiveness analysis of the intervention methods was conducted with the use of Digital Balance Analyzer (DBA) for the assessment of statical balance. 36 orienteers (12 to 18 years old) were randomized in three groups to an intervention, after being assessed at baseline and then reassessed one week later. Static balance improvements are only when using osteopathy and ankle joints subtalar somatic dysfunction correction together with balance exercises. Separate osteopathy or balance exercises will not give results as effective as the combination of these two effects.